Two critical thinking models—probing questions and conceptualization—adding 4 skillsets to the teacher's armamentarium. Issue 7 (18th May 2020) - Johnsen, David C.; Flick, Kristen; Butali, Azeez; Cunningham‐Ford, Marsha A.; Holloway, Julie A.; Mahrous, Ahmed; Marchini, Leonardo; Clancy, James M.
Abstract: Critical thinking is ubiquitous in patient care. One track for critical thinking develops skillsets emulating the thought process of the master clinician using probing questions and has been offered in treatment planning, literature search, and critique, risk assessment in caries and geriatrics, technology decision‐making, EBD, and IPP. This paper offers 2 additional critical thinking skillsets following this emulation model in social work and ethics. Conceptualization, another form of critical thinking, is also ubiquitous in health care, yet almost no literature exists to guide learning and assess performance on conceptualization. This paper introduces for discussion 2 examples of conceptualization—"How and how much does this situation differ from the ideal?" and "How does the student/practitioner conceptualize the outcome prior to the imminent procedure?" —used continually by the practitioner in patient care situations. The result is 4 additional critical thinking skillsets at different stages of development in the armamentarium for the teacher.